The Fossil Flora of Great Britain : Or, Figures and Descriptions of the Vegetable Remains Found in a Fossil State in this Country. Volume 1 - Lindley, John, 1799-1865; Hutton, William, 1797-1860 (Place of publication not identified : publisher not identified, 1831)
Employed early on in his career by Sir Joseph Banks, the botanist John Lindley (1799-1865) went on to conduct important research on the orchid family and also recommended that Kew Gardens should become a national botanical institution. This pioneering three-volume work of palaeobotany, first published between 1831 and 1837, catalogues almost 300 species of fossil plants from the Pleistocene to the Carboniferous period. The geologist and palaeontologist William Hutton (1797-1860), with whom Lindley collaborated, was responsible for collecting the fossil specimens from which the 230 plates were drawn. The first serious attempt at organising and interpreting the evidence of Britain's primeval plant life, this resource is notable also for its prefatory discussion of topics such as coal seams and prehistoric climate. Volume 1 opens with a context-setting introduction and list of genera, followed by the descriptions of plates 1-79.
Includes index.
Keywords: Plants, Fossil -- Great Britain